Juridical Analysis of Saudi Arabia's Intervention in Yemen's Internal Conflict Reviewed According to International Law Provision - Alfianto, Muhammad Hadi; Arifin, Ridwan; Nte, Ngboawaji Daniel (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2024)
Saudi Arabia's intervention in the internal conflict in Yemen has been the focus of attention due to its significant humanitarian and political implications. The continuation of this conflict has raised the need for an objective evaluation of the role played by Saudi Arabia, especially the extent to which it complies with United Nations (UN) rules and regulations. The conflict in Yemen has created profound humanitarian impacts, including starvation and the suffering of countless people. Therefore, this essay aims to conduct a thorough analysis of Saudi Arabia's intervention in Yemen with a particular focus on the legality and effectiveness of their actions. By examining Saudi Arabia's level of compliance with international law, especially the norms upheld by the UN, we can better understand whether their actions are in line with prevailing international norms. In addition, the impact of this intervention on the Yemeni population as a whole will also be explored. This comprehensive analysis is expected to provide an in-depth understanding of Saudi Arabia's contribution to the Yemen conflict, both in terms of its legality and humanitarian impact. In this way, we can develop a balanced and rational view of Saudi Arabia's role in the context of the protracted conflict in Yemen.